Psychological factors in functional hypothalamic amenorrhea: A systematic review and meta-analysis - Bonazza, Federica; Politi, Giuliana; Leone, Daniela; Vegni, Elena; Borghi, Lidia (Frontiers in Endocrinology, 2023)
Background: Psychological factors have been found to be associated with functional hypothalamic amenorrhea (FHA); however, their role in the onset or persistence of FHA is still understudied. The study aims to assess the associations of psychological factors with the presence vs the absence of FHA. Methods: A systematic literature search has been conducted across the major databases (PubMed, PsycINFO, Scopus, and Embase) to explore the psychological factors associated with FHA. The search was limited to English-written articles published from 2000 onwards. Articles were selected based on stringent inclusion/exclusion criteria. After data extraction, meta-analysis and meta-synthesis were conducted. Results: Of 349 retrieved articles, eight studies were included. Findings indicate that the main psychological factors associated to FHA seem to be depression and eating attitudes, especially drive for thinness. FHA women present higher levels of anxiety, sleep disorders, dysfunctional attitudes, and alexithymia. The meta-analysis on drive for thinness revealed that the pooled MD across the studies was statistically significant both in the fixed 0.63 (95% CI: 0.31–0.95) and random model 0.70 (95% CI: 0.13–1.26). Likewise, as for depression, the pooled MD across the studies was statistically significant both in the fixed 0.60 (95% CI: 0.36–0.84) and random model 0.61 (95% CI: 0.20–1.01). Discussion: Findings showed the association of psychological factors and FHA and recognized their involvement in the persistence of the disorder. A multidisciplinary approach should involve a collaborative process between gynecologists, clinical psychologists, and psychiatrists, from diagnosis to treatment. Longitudinal studies should be implemented with a comparison/control group or by including clinical psychologists in the psychological assessment and study design.